2018
DOI: 10.1186/s12871-018-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrathecal dexmedetomidine on the dose requirement of hyperbaric bupivacaine in spinal anaesthesia for caesarean section: a prospective, double-blinded, randomized study

Abstract: BackgroundStudies have shown that dexmedetomidine (Dex) can prolong the duration of analgesia when added to local anaesthetic as an adjuvant in a central or peripheral nerve block. We hypothesized that intrathecal Dex can reduce the ED95 of spinal hyperbaric bupivacaine. Therefore, we conducted this prospective, double-blinded, randomized study to verify our hypothesis.MethodsNinety patients were allocated into the Dexmedetomidine group (received bupivacaine + 5 mcg dexmedetomidine) and the Control group (rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 36 publications
1
40
0
2
Order By: Relevance
“…But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). Zhou et al found that dexmedetomidine can reduce the traumatic stress response and immune suppression caused by surgery and has a protective effect on the spinal cord in spinal surgery (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dose of 2.5 -10 gm is considered optimal for intrathecal use by many authors. [3][4] So we took 5gm Dexmedetomidine as optimum dose for intrathecal addition to Bupivacaine in this study. 13 In present study Group D received intrathecal hyperbaric Bupivacaine 0.5% 9 mg (1.8 ml) and Dexmedetomidine 5µgm while group C received intrathecal hyperbaric Bupivacaine 0.5% 9 mg (1.8 ml) and 0.9% saline.…”
Section: Discussionmentioning
confidence: 99%
“…They potentiate the effect of local anaesthetics and allows a decrease in the required dose. [3][4] Both of these drugs are well studied as intrathecal adjuvants in orthopaedic and general surgeries. 5 Dexmedetomidine, is 8 times more selective α 2 adrenergic receptor agonist as compared to Clonidine, thus it can be safely used as intrathecal adjuvant in caesarean surgeries due to its limited effects on respiratory system and level of patient's consciousness during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis ultimately included 10 RCTs (Figure 1) with a total of 706 patients, of which 9 studies [10,21,22,[24][25][26][27][28][29] used bupivacaine and 1 study [23] used lidocaine for spinal anesthesia. In these studies, 6 compared DEX with saline, and the remaining 4 studies compared DEX with tramadol and saline, clonidine with DEX and saline and fentanyl, DEX with morphine and saline, and DEX with saline and fentanyl, respectively.…”
Section: Characteristics Of Eligible Studies and Risk Of Biasmentioning
confidence: 99%